2017
DOI: 10.1038/s41598-017-16164-0
|View full text |Cite
|
Sign up to set email alerts
|

Extensive gene flow of white-backed planthopper in the Greater Mekong Subregion as revealed by microsatellite markers

Abstract: The white-backed planthopper (WBPH), Sogatella furcifera (Horváth), is a destructive pest of rice in the Greater Mekong Subregion (GMS) countries including Cambodia, Laos, Myanmar, Thailand, Vietnam, and China’s Yunnan Province. Our previous study not only confirmed the immigration sources of the WBPH in China’s Yunnan Province were from Myanmar, Vietnam, and Laos, but also indicated that Cambodia was likely an additional migration source. To further clarify the migration sources and patterns of the WBPH in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 23 publications
4
11
0
Order By: Relevance
“…The AMOVA result indicated that there is only 4.40% (mtDNA) and 0.19% (SNP) genetic variation when all of the samples were grouped based on the geographic criteria. These results con rmed previous ndings that WBPH migrates between the counties in GMS and China [9].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The AMOVA result indicated that there is only 4.40% (mtDNA) and 0.19% (SNP) genetic variation when all of the samples were grouped based on the geographic criteria. These results con rmed previous ndings that WBPH migrates between the counties in GMS and China [9].…”
Section: Discussionsupporting
confidence: 91%
“…The genome SNP markers (2b-RAD) analysis showed that a heterozygosity de cit existed in all populations. This result may be explained by demographic expansion, and it is consistent with [9] who also found that WBPH had a heterozygosity de cit during expansion. These ndings suggest that WBPH may have non-random mating and intense migration in the sampled populations.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…For example, most insects have a high dispersal ability and thus high gene flow between different populations. This is especially true in migratory insects (Li et al, ; Yin et al, ) and is obviously different from the empirical analysis used on plant populations. In addition, many other factors including demographic history, intrinsic life‐history traits, and overall population characteristics should also be considered (Nazareno et al, ).…”
Section: Introductionmentioning
confidence: 94%
“…Widespread species with high dispersal capacity often show less pronounced spatial genetic structure with lower F ST distributions (e.g., Llewellyn et al, 2003;Vorburger, Lancaster, & Sunnucks, 2003;Yin et al, 2017). Minimal genetic structuring in P. vittatum was anticipated due to the species' high abundance and mobility across pastures and agricultural areas of Australia (Farrow, Nicolas, & Dowse, 1982;Yadav et al, 2018).…”
Section: Temperature and Land Cover Effects On Genetic Connectivitymentioning
confidence: 99%